Temperature-controlled exfoliation of graphite oxide: studies of defects and transport properties of graphene oxide. (1st May 2022) - Kumar, Satendra; Goswami, Manoj; Singh, Netrapal; Siddiqui, Hafsa; Natarajan, Sathish; Ashiq, Mohammad; Kumar, Surender
Abstract: The quality, structural defects, and transport properties of GO can be tailored by maintaining ultrasonic bath temperature. Herein, the effect of temperature-controlled exfoliation on the structural defects and transport properties of the resulting graphene oxide (GO) sheets are examined. The large crystallite size (12.23 nm) and low defect density (2.16 × 10 11 cm −2 ) are found at 20 °C exfoliations. Highly oriented GO sheets were exfoliated at 20 °C which was confirmed through Bernal-stacking proportions (∼30%). Furthermore, electrical transport properties are high at 10 °C exfoliation temperature while optimum at other temperatures, calculated through impedance spectroscopy. Comparatively, smooth, wrinkle-free, and lesser bulges are found at 20 °C and 30 °C exfoliation temperatures.